2020
DOI: 10.3390/pharmaceutics12040387
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Lung Residence Time of Highly Permeable Molecules after Nebulization: Example of the Fluoroquinolones

Abstract: Pulmonary drug delivery is a promising strategy to treat lung infectious disease as it allows for a high local drug concentration and low systemic side effects. This is particularly true for low-permeability drugs, such as tobramycin or colistin, that penetrate the lung at a low rate after systemic administration and greatly benefit from lung administration in terms of the local drug concentration. However, for relatively high-permeable drugs, such as fluoroquinolones (FQs), the rate of absorption is so high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…To improve specific liposomal uptake and intracellular routing, the addition of fucose-derived targeting ligands is appealing because of their ability to bind to CLRs expressed on the surface of myeloid antigen-presenting cells. [30,38,18] Such receptors include the macrophage mannose (CD206) and DC-SIGN (CD209) receptors present on alveolar macrophages that serve as entry ports and reservoirs of mycobacteria. [39,40] Following this pathway, Duran et al demonstrated that addressing the CD206 receptor will direct fucosylated liposomes and associated antibiotics to early and late endosomes where mycobacteria typically persist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve specific liposomal uptake and intracellular routing, the addition of fucose-derived targeting ligands is appealing because of their ability to bind to CLRs expressed on the surface of myeloid antigen-presenting cells. [30,38,18] Such receptors include the macrophage mannose (CD206) and DC-SIGN (CD209) receptors present on alveolar macrophages that serve as entry ports and reservoirs of mycobacteria. [39,40] Following this pathway, Duran et al demonstrated that addressing the CD206 receptor will direct fucosylated liposomes and associated antibiotics to early and late endosomes where mycobacteria typically persist.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Another aspect to be considered is the ability of fluoroquinolones including LVX to rapidly permeate the alveolar epithelium requiring formulation approaches to enhance lung residence time. [18] A process often heeded only late in the development process is the demand for an inhalable dosage form with optimized aerodynamic properties and sufficient storage stability. The latter is particularly relevant for mycobacterial infections that mainly occur in low-income countries with inappropriate storage conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Within a short-term incubation, IA induces membrane stress, which PA can balance by stress-response gene up-regulation [31]. Despite the short in vivo half-life, Cipro-a potent antibiotic, which inhibits bacterial DNA topoisomerase and DNA-gyrase [38]-has been formulated as a dry-powder [18] or liposomal inhalation therapy [16] for the treatment of pulmonary infections [39]. Depending on the Cipro concentrations and the biofilm growing techniques, the outcomes of the studies addressing Cipro transport through biofilms have shown heterogeneous outcomes [37,40].…”
Section: Discussionmentioning
confidence: 99%
“…Triazoles, which have a high permeability across the respiratory barrier, are less attractive to inhale as a solution, since a low residence time in the lungs is obtained. Molecules with a high respiratory barrier permeability need to be delivered as solid particles with a slow dissolution/release rate, or as advanced formulations that can control permeability to increase their residence time in the lungs after inhalation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%